2007
DOI: 10.1177/0265407507072576
|View full text |Cite
|
Sign up to set email alerts
|

Attachment orientations, sexual functioning, and relationship satisfaction in a community sample of women

Abstract: The current research focuses on the detrimental effects of attachment insecurities on sexuality and relationship quality. A community sample of 96 women completed self-report scales tapping attachment orientations; relationship satisfaction; sex-related affect and cognitions; and sexual functioning. Findings indicate that although both attachment anxiety and avoidance were associated with aversive sexual affect and cognitions, attachment anxiety was more detrimental to sexual functioning. In addition, only att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
147
5
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(177 citation statements)
references
References 32 publications
15
147
5
10
Order By: Relevance
“…Secure individuals are less likely to be unfaithful and more likely to enjoy sexual activity within a committed relationship than insecure individuals (Brennan & Shaver, 1995;DeWall et al, 2011). Taken together, these findings suggest that attachment security is beneficial for establishing happy, healthy, and sexually satisfying long-term romantic relationships (e.g., Birnbaum, 2007;Butzer & Campbell, 2008;Davis et al, 2006). …”
Section: Cnm and Attachmentmentioning
confidence: 76%
“…Secure individuals are less likely to be unfaithful and more likely to enjoy sexual activity within a committed relationship than insecure individuals (Brennan & Shaver, 1995;DeWall et al, 2011). Taken together, these findings suggest that attachment security is beneficial for establishing happy, healthy, and sexually satisfying long-term romantic relationships (e.g., Birnbaum, 2007;Butzer & Campbell, 2008;Davis et al, 2006). …”
Section: Cnm and Attachmentmentioning
confidence: 76%
“…Indeed, both attachment anxiety and avoidances are associated with greater dissatisfaction with sexual interactions [21,22,23], and more negative affect concerning sexual experiences [15,24,25]. In their systematic review of the literature examining attachment and sexual functioning for this journal, Stefanou and McCabe [4] concluded that across studies that focused on a variety of satisfaction and functioning measures, attachment insecurity (avoidance and anxiety) was consistently associated with decreased reports of global evaluations of sexual satisfaction across relationship types (e.g., dating, married).…”
Section: Attachment and Sexual Satisfactionmentioning
confidence: 99%
“…To potvrđuje i meta-studija u kojoj je identifikovana vi-soka pozitivna korelacija anksioznosti i negativnih indikatora kvaliteta veze (Li & Chan, 2012). Istraživanja pokazuju i da anksiozno vezane osobe koriste seksualne odnose u cilju redukcije nesigurnosti i umanjivanja straha od napuštanja, te uspostavljanja intenzivne bliskosti, brižnosti, odobravanja i partnerovog ohrabrenja (Birnbaum, 2007;Davis et al, 2004;Feeney & Noller, 2004;Schachner & Shaver, 2004).…”
unclassified
“…To potvrđuju rezultati meta-studije (Li & Chan, 2012) gde su registrovane visoke negativne korelacije izbegavanja sa pozitivnim indikatorima kvaliteta partnerske relacije. Izbegavajuće vezane osobe imaju i niži nivo seksualne intimnosti i prijatnih osećanja tokom seksa (Birnbaum, 2007;Birnbaum, Reis, Mikulincer, Gillath, & Orpaz, 2006;Mikulincer & Goodman, 2006), te doživljavaju seksualne odnose neprijatnim (Shaver & Mikulincer, 2007). Osobe čiji partneri imaju izraženo izbegavanje izveštavaju o nižem seksualnom zadovoljstvu, za razliku od osoba čiji partneri imaju izraženu anksioznost (Butzer & Campbell, 2008).…”
unclassified